1997
DOI: 10.2307/2329494
|View full text |Cite
|
Sign up to set email alerts
|

Tick Size, Share Prices, and Stock Splits

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 36 publications
5
81
2
5
Order By: Relevance
“…According to this theory, without these specialists, the intraday pattern of spread could be flat and keep narrow. The relative spread (Note 7) in our sample (0.271%) is lower compared with the results of Angel (1997), in which the relative bid-ask spread median is calculated to equal 0.65% for major market indices of fifteen countries. The mean of volatility for five stocks on the ASX market is 0.747, while the value on Swiss market is 0.482, as surveyed by Ranaldo (2004).…”
Section: Descriptive Statisticscontrasting
confidence: 76%
“…According to this theory, without these specialists, the intraday pattern of spread could be flat and keep narrow. The relative spread (Note 7) in our sample (0.271%) is lower compared with the results of Angel (1997), in which the relative bid-ask spread median is calculated to equal 0.65% for major market indices of fifteen countries. The mean of volatility for five stocks on the ASX market is 0.747, while the value on Swiss market is 0.482, as surveyed by Ranaldo (2004).…”
Section: Descriptive Statisticscontrasting
confidence: 76%
“…Others discuss the existence of an optimal tick size. Angel (1997) and Anshuman and Kalay (2002) both conclude that the optimal tick size must minimize investors' trading costs. But while Angel's model indicates that the optimal tick size is an increasing function of firms' market values and idiosyncratic risks, Anshuman and Kalay (2002) focus on the trade-off between adverse selection and discreteness related costs.…”
Section: The Significance Of Tick Sizementioning
confidence: 99%
“…Angel (1997) and Anshuman and Kalay (2002) note that a tick size that is too small may not be sufficient to compensate liquidity provision in presence of informed traders. Seppi (1997) and Cordella and Foucault (1999) produce models to convey these concerns and show that the optimal tick size should not be zero.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this area have shown that increasing the tick size (1) leads to an increase in market making profits and hence to an increase in liquidity supply by the latter (Bollen et al 2003) and Anshuman and Kalay 1998) and (2) helps market makers to recover fixed costs. At the same time, Angel (1997) shows that in a large tick regime, investors are able to supply liquidity by placing limit orders. In Table 3, Panel C, we conclude this section by presenting the studies concerned with the general implications of a minimum tick on market making activities.…”
Section: Tick Size Changes and Market Liquiditymentioning
confidence: 99%